Determinants of the readability and comprehensibility of risk disclosures: evidence from Portuguese listed companies - Oliveira, J. S. O.; Azevedo, G. M. C.; Ferreira, A. C. S.; Martins, S. P. H.; Pinto, C. R. A. A. (International financial reporting standards and new directions in earnings management, 2019)
The chapter intends to determine if managers make use of impression management strategies to hide or obfuscate risk disclosures through the analyses of the risk information disclosed by Portuguese non-financial listed companies. A content analysis of the management reports, notes to the financial statements, and corporate governance reports of companies listed at Euronext Lisbon, in the years 2007, 2010, and 2013 was carried out. Findings indicate that the understandability of the risk information is positively associated with the company's size. Results also indicate that there is a negative association between the readability of risk information disclosed and the company's size and industry.